Cichorium glandulosum Ameliorates HFD-Induced Obesity in Mice by Modulating Gut Microbiota and Bile Acids - Zhong, Yewei; Emam, Hurxida; Hou, Wenhui; Yan, Junlin; Abudurexiti, Adalaiti; Zhang, Rui; Qi, Shuwen; Lei, Yi; Ma, Xiaoli (Journal of medicinal food, 2024)
Obesity is an ongoing global health problem, and (CG, chicory) is traditionally used as a hepatoprotective and lipid-lowering drug. However, there is still a lack of research on the role of CG in the treatment of obesity. In the present study, we found that CG significantly delayed weight gain and positively affected glucolipid metabolism disorders, serum metabolism levels, and the degree of liver and kidney oxidative stress in high-fat diet (HFD) mice. Further examination of the effects of CG on intestinal microenvironmental dysregulation and its metabolites in HFD mice revealed that the CG ethanol extract high-dose group (CGH) did not have a significant regulatory effect on short-chain fatty acids. Still, CGH significantly decreased the levels of 12α-OH/non-12α-OH bile acids and also found significant upregulation of proteobacteria and downregulation of cyanobacteria at the phylum level. CG may have ameliorated obesity and metabolic abnormalities in mice by repairing gut microbiota dysbiosis and modulating bile acid biosynthesis.